The contribution of toll-like receptor 2 on Helicobacter pylori activation of the nuclear factor-kappa B signaling pathway in gastric epithelial cells. (September 2016) - Li, Shu; Cao, Mei; Song, Liju; Qi, Panpan; Chen, Chong; Wang, Xuege; Li, Ningzhe; Peng, Jingshan; Wu, Daoyan; Hu, Guoku; Zhao, Jian
Abstract: Helicobacter pylori ( H. pylori ) is a spiral shaped gram-negative bacterium that induces immune responses in the gastric mucosa. Toll-like receptors (TLRs) play important roles in mediating inflammatory cytokines by recognition of conserved molecular patterns on bacteria. Changes in the expression of toll-like receptor (TLR) 2, TLR4 and the relative inflammatory cytokines were analyzed in normal gastric epithelial GES-1 cells following treatment with H. pylori or Escherichia coli lipopolysaccharide ( E. coli LPS) in order to investigate the contribution of TLRs in recognizing and mediating the inflammatory response to H. pylori, and study the differences in TLRs' performance between H. pylori and E. coli . Specific inhibitors for the declines in TLR2 and TLR4 were also employed. The results showed that H. pylori infection increased TLR2 expression in GES-1 cells, but TLR4 remained unchanged regardless of H. pylori or TLR2 small interfering RNA treatment. Furthermore, the secretion of cyclooxygenase-2 (COX-2) induced by H. pylori was inhibited by declines in TLR2, but not in TLR4. In conclusion, TLR2 plays an even more important role than TLR4 not only in recognizing H. pylori, but also in the induction of inflammatory cytokines initiated by H. pylori . However, both TLR2 and TLR4 are necessary in mediating the inflammatory response to E. coli LPS. Highlights: Helicobacter pylori is mainly recognized by TLR2 but not TLR4. Escherichia coli LPS is recognized by both TLR2 and TLR4 with TLR4 playing the main role. Both H. pylori and E. coli LPS stimulation enhance COX-2 and iNOS expression. TLR2 is involved in the increment of COX-2 infected by H. pylori. COX-2 induction by E. coli LPS is dependent on both TLR2 and TLR4.